2016
DOI: 10.1186/s40064-016-1677-8
|View full text |Cite
|
Sign up to set email alerts
|

Is semirigid ureteroscopy sufficient in the treatment of proximal ureteral stones? When is combined therapy with flexible ureteroscopy needed?

Abstract: The goals of this study were to examine cases of proximal ureteral stones in which semirigid or flexible ureteroscopes alone were insufficient for endoscopic treatment, requiring the combination of both. A total of 137 patients were retrospectively evaluated. Holmium laser was used as the energy source for stone fragmentation. Each operation was begun with a 6/7.5 Fr semirigid ureteroscope (URS), and continued with a 7.5 Fr flexible URS in those procedures that failed to reach the stone or push-up. Double J st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The decision regarding the use of antiretropulsed measures was made according to the preference of the surgeon and the estimated intraoperative risk of stone migration. This risk is higher for proximal stones located in a dilated ureter [7].…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The decision regarding the use of antiretropulsed measures was made according to the preference of the surgeon and the estimated intraoperative risk of stone migration. This risk is higher for proximal stones located in a dilated ureter [7].…”
Section: Resultsmentioning
confidence: 98%
“…It was shown that f-URS and ureteral sheaths were valuable instruments for treating upper stones (Table 2) Discussion SR ureteroscopes with size less than 9 F are excellent instruments for endoscopy of the distal ureter [1]. When modern lithotripters are used fragmentation of lower ureteral stones is feasible in 90-100% of the cases [7]. Endoscopy of the upper tract only with the SR scope may be a challenging intervention, which fails in approximately 32% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations